Rancang Bangun Aplikasi Game Tajen Berbasis Android Menggunakan Artificial Intelligence - Gandhi Arsawiguna, Made; Agung Cahyawan Wiranatha, A. A. Kt.; Suar Wibawa, Kadek (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.2 Agustus 2015, 2015)
Tabuh Rah is a culture and a rituals in Bali to present the blood of animals through a cockfight or Tajen. However there are certain people who abuse Tajen for gambling, and that give a misunderstanding of the Tajen function for people. The rapid development of technology has also led to a lack of public attention to their own culture. Overcome these problems, the use of technology through an Android-based gaming is the right solution. Tajen Game is an fighting Android based game by choosing a cock as character to play the game, spurs and installation methods, and a good day to try the cockfight based on the calculation of Saptawara and Pancawara. This  game  was  made  to  introduce the  main  function of  Tajen.  Corona  SDK (Software Development Kit) is the software that use to create his game and using the Lua Programming Language. The quality of Tajen Game based on the respondents' assessment is good, with the percentage of the graphic aspect of the game by 58%, entertainment aspects by 70%, and the content aspects by 57%.
Keywords: Budaya, Tajen, Android, Artificial Intelligence